PD-1/PD-L1 inhibitors plus bevacizumab plus chemotherapy versus PD-1/PD-L1 inhibitors plus chemotherapy for advanced non-small cell lung cancer: a phase 3 RCT based meta-analysis - Song, Chao; Qiu, Yuan; Fan, Huan; Han, Yongqing (Frontiers in Oncology, 2025)
BackgroundCombining PD-1/PD-L1 inhibitors with chemotherapy (PIC) is a standard first-line treatment for advanced non-small cell lung cancer (NSCLC). The addition of bevacizumab to this regimen (PD-1/PD-L1 inhibitors+bevacizumab+chemotherapy [PIBC]) remains controversial regarding its potential to enhance antitumor efficacy in clinical practice. This meta-analysis aims to compare the antitumor effectiveness and safety profiles of PIBC with PIC.MethodsWe systematically searched six databases to identify eligible RCTs. The primary outcomes were overall survival (OS) and progression-free survival (PFS), while the secondary outcomes included treatment responses and adverse events (AEs).ResultsThree RCTs (IMpower150, jRCT2080224500, and ORIENT-31) comprising a total of 1529 patients were analyzed. The PIBC regimen significantly improved PFS (hazard ratio [HR]: 0.76 [0.66, 0.87], P < 0.0001), objective response rate (risk ratio [RR]: 1.36 [1.22, 1.51], P < 0.00001), and disease control rate (RR: 1.06 [1.00, 1.12], P = 0.04). The PFS rates were also higher in the PIBC group at 6 and 18 months. Both groups showed similar results in terms of OS, 3–36 month OS rates, and total AEs. However, the PIBC group exhibited a higher incidence of grade 3–5 AEs, serious AEs, grade 3–5 treatment-related AEs (TRAEs) and serious TRAEs. The most frequent grade 3–5 AEs in the PIBC group included anorexia (36.40%), decreased neutrophil count (16.25%), neutropenia (13.50%), reduced white blood cell count (12.12%), and febrile neutropenia (9.42%).ConclusionsPIBC appears to be better than PIC for advanced NSCLC offering improved PFS and response rates (ORR and DCR). However, its higher incidence of AEs requires cautious attention.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024559146, identifier CRD42024559146.